Analysis of the Influence of Perception and Operational Services on Electric Car Purchase Decisions in Jabodetabek - Hutabarat, Igleysias Rheinhart; Nusraningrum, Dewi (Journal of Sustainable Economic and Business, 2025)
Objective: The purpose of this study is to examine how attitudes, subjective norms, behavioral control, perceived utility, and convenience of use, as mediated by operational services, affect decisions to buy electric cars in the Jabodetabek region.Methodology: This study falls under the area of quantitatively based explanatory research. Customers who deal with different brands of electric automobiles in Jabodetabek make up the research population. 105 responders made up the sample under analysis. Smart PLS software version 3.0 was used to analyze the data using the Structural Equation Modeling (SEM) approach.Results: The results of the study demonstrate that people's decisions to purchase electric vehicles are considerably and favorably influenced by their attitudes, behavioral control, and perceived usefulness. However, subjective norms and perceived ease of use do not have a favorable and significant impact on the decision to purchase. Furthermore, even while operational services are thought to be more than sufficient, they neither mediate nor affect the relationship between the decision to purchase an electric car and behavioral control, attitude, subjective norms, perceived utility, and ease of use.Conclusion: Operational services cannot mediate the relationship between perceived usefulness, ease of use, attitude, subjective norms, and behavioral control with electric car purchase decisions. However, operational services remain an important aspect to ensure consumer satisfaction.